Intersectionality and Birth in Latin America: A Research Protocol on Maternal Health of Indigenous and Afro-Descendant Women in La Guajira, Colombia - Mariana Anginho Évora (Social Sciences)
This article presents a research protocol focusing on the maternal health of Indigenous wayuu and Afro-descendant women in the region of La Guajira, Colombia. Following a decolonial approach and expecting the project to contribute to the field of sociology of birth, in this paper I propose to discuss the mobilized literature, methodologies, and ethical concerns critically and reflectively. This research aims to understand how the various paradigms of birth interact in contemporary times and how these interactions affect women’s experiences and expectations; to contribute to knowledge about birth and maternity among the Indigenous and Afro-descendant people of Colombia; and to evaluate existing maternal health indicators while proposing new ones that respond to the criteria and needs of the population under study. An ethnography and narrative interviews will be conducted with Indigenous wayuu and Afro-descendant women and health professionals in La Guajira, a department of Northern Colombia. Additionally, statistical birth analysis using data available from the National Statistical System of Colombia will be implemented. The results will be combined, co-created with study participants, and disseminated to a variety of audiences.